INTERACTIVE ACTIVITIES FOR TEACHING CHILDREN - Hertiki, Hertiki (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2017)
Young learners have very little opportunities in using English for communication in Indonesian classrooms. To overcome the problem, the teacher should think of interactive activities to encourage students in class. However, as teachers, they have to be aware in choosing the suitable activities for young learners. There are lots of activities for young learners such as: games, TPR (movement), music/songs, coloring, drawing, making things, and sorting/putting into categories. Well-chosen activities are helpful as they give children to have fun and at the same time allowing them to practice language skills. The activities that work in class should rules, instructions, time management, praises and rewards.This paper provides a brief overview ofinteractive activities that can be used to encourage young learners to participate more in class.These are the following selected activities that used for teaching English for young learners such as but first, mime a monster, five little elephants, draw the picture, draw your friendÃ¢â‚¬â„¢s life, bingo, running dictation, hues your friendÃ¢â‚¬â„¢s habit and Ã¢â‚¬Å“truth or dareÃ¢â‚¬Â. In conclusion, it is hoped that all activities can make children become more active and they are willing to participate during the English lesson.